Tort Compensation in the United States and England: Goal or Means? - Segal, Boaz (American Journal of Trade and Policy, 2021)
The modern state exists and acts on behalf of its citizens. No longer is it the state of a sole ruler acting on his or her own behalf and for his or her own sake. Rather, it is a civil state whose role is to preserve the rights of its citizens and to maximize their welfare. An important instrument for the goal of realizing these roles is the government authority held by the state. Consequently, the modern state exercises extensive government authority in social and economic life. The widening of the areas of activity in which it is involved and over which it exercises its authority raises the question of the desirable scope of state liability for the negligent exercise of this authority. In this paper, I analyze the scope of tort liability of public agencies and public authorities in the United States and England. The innovation proposed in this article is twofold for, although the scope of liability of public agencies has been extensively surveyed and analyzed in the academic literature, these surveys and analyses were for the most part conducted by means of organizing the development of the relevant case law along a timeline. This article adopts a different approach, examining the scope of liability of public agencies according to their areas of activity. Accordingly, the abundant court judgments are classified into varied areas of government activity. This technique allows for fine, precise inferences to be drawn with regard to the level of liability of public agencies. It can be started already at this stage that, as a whole, the fundamental conclusion of this article is that in both the United States and England the remnants of the traditional doctrine, that of sovereign or crown immunity, are marked. An analysis of the law in these countries shows that to this day, public agencies still enjoy extensive protections against tort claims and that the general approach there has always been to limit liability. The second innovation included in this article is, in a nutshell, the suggestion of a possible reason for the prevalence of this doctrine in the United States and England. I argue that this reason may be the manner in which each judicial system perceives the role of the instrument of tort compensation. Accordingly, I contend that compensation is perceived in the United States and England as a means to achieve the goals of tort law, rather than as an independent goal standing on its own merit.
Keywords: Tort compensation; public agencies; public authorities; scope of public agency liability